2018
DOI: 10.1093/ofid/ofy210.451
|View full text |Cite
|
Sign up to set email alerts
|

442. The Results of a Primary Care-based Screening Program for Trypanosoma cruzi in East Boston, Massachusetts

Abstract: BackgroundThis study reports the outcomes of the Strong Hearts pilot project to integrate screening for Trypanosoma cruzi into a primary care setting and facilitate referral for treatment at East Boston Neighborhood Health Center.MethodsContinuing education about Chagas disease was offered to healthcare providers, and community-based outreach was provided. One-time screening for all patients ≤50 years old who lived in Mexico, South or Central America for ≥6 months was recommended. The initial screening test wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Current practice in Latin America prioritizes diagnosis and treatment of children 15 years old or younger, but the vast majority of infected individuals in the United States are adults. In the sparse available community screening data, the T. cruzi prevalence in Latin American adults 40 years or younger was 0.64 to 0.95% compared to 1.42 to 1.78% among those older 40 years(280,281). In limited community screening to date, no infections have been detected among children(281).Tertiary prevention has had a major impact on the survival and quality of life of persons living with T. cruzi infection in Latin America(340), and the experience of a dedicated center of excellence based in the cardiology service of a large Los Angeles hospital confirms this model in the United States (310, 311, 341-343).…”
mentioning
confidence: 98%
“…Current practice in Latin America prioritizes diagnosis and treatment of children 15 years old or younger, but the vast majority of infected individuals in the United States are adults. In the sparse available community screening data, the T. cruzi prevalence in Latin American adults 40 years or younger was 0.64 to 0.95% compared to 1.42 to 1.78% among those older 40 years(280,281). In limited community screening to date, no infections have been detected among children(281).Tertiary prevention has had a major impact on the survival and quality of life of persons living with T. cruzi infection in Latin America(340), and the experience of a dedicated center of excellence based in the cardiology service of a large Los Angeles hospital confirms this model in the United States (310, 311, 341-343).…”
mentioning
confidence: 98%
“…Our study showed that while overall disease prevalence is low, in selected groups, there is a need to initiate screening and follow-up processes when appropriate. Another primary care-based screening pilot program in Boston found 3.8% positive screening tests, demonstrating the feasibility of incorporation of CD screening in primary care in non-endemic settings [45]. Custom-made interdisciplinary initiatives that align with local goals and health projects are feasible, effective, and should be promoted to screen as many people as cost-effectively as possible in primary care settings.…”
Section: Discussionmentioning
confidence: 99%
“… 10 In Boston, of 2183 individuals screened who had lived in Latin America for at least 6 months, 19 (0.9%) were confirmed positive. 5 …”
Section: Discussionmentioning
confidence: 99%
“…We sought to perform a Chagas disease seroprevalence study and risk factor assessment among Latin American children living in Suffolk County, New York. We are aware of only one other seroprevalence study in the United States that enrolled children, 5 underscoring the tremendous gap in knowledge of pediatric Chagas disease in the US.…”
Section: Introductionmentioning
confidence: 99%